Optimizing Value-Added Tax Revenue Through Synergy of Self-Assessment System, Restitution, and Number of Taxable Entrepreneurs - Melia Nur Maulida; Nurul Alifah; Moh Yudi Mahadianto; Asep Basuki (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the effect of the self-assessment system, VAT restitution, and the number of taxable entrepreneurs (PKP) on Value Added Tax (VAT) revenue at the Cirebon One Primary Tax Service Office. Using a quantitative approach and 49 secondary data samples obtained from December 2020 to December 2024, the research applies multiple linear regression analysis to assess the relationships among these variables. The findings suggest that the self-assessment system contributes significantly to increasing VAT revenue. Allowing taxpayers to independently calculate, pay, and report their taxes appears to improve compliance and enhance state revenue collection. In contrast, VAT restitution shows a significant negative effect on revenue, indicating that larger refunds are associated with reduced funds entering the state treasury. Meanwhile, the number of registered taxable entrepreneurs does not significantly impact VAT revenue. This result may reflect ongoing challenges such as low compliance among businesses, reliance on tax consultants to minimize obligations, and limited understanding of tax responsibilities. The study highlights the importance of supporting effective self-assessment mechanisms and evaluating refund policies to balance fairness and fiscal sustainability.